findjob helping high school graduates to find a job in the BPO industry - Fabian, John Neil R.
The purpose of this research is to help high school graduates to find a job in the BPO Industry. The number one reason why high school graduates stop their studies is because of financial problems. Because of that, they are having a hard time looking for a stable job, a job that can sustain their needs and wants. Through this research, the researcher came up with a design problem which is "how can I help high school graduates to find a job in the BPO Industry around Metro Manila." The researcher choose to recommend BPO jobs because it offers a good salary, benefits and they accept high school graduates and that is a good start and opportunity for high school graduates.